2013
DOI: 10.5114/aoms.2012.30834
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-phosphate metabolism parameters and erythrocyte Ca 2+ concentration in autosomal dominant polycystic kidney disease patients with normal renal function

Abstract: IntroductionThe aim of this study was to assess calcium-phosphate metabolism of autosomal dominant polycystic kidney disease (ADPKD) patients with a special consideration to the following serum parameters: calcium (Ca2+), inorganic phosphate (Pi), parathyroid hormone (PTH) and intracellular erythrocyte calcium ([Ca2+]i) concentrations.Material and methodsThe study included 49 adult ADPKD patients (19 males, 30 females) aged 36 ±11 years with normal renal function and no diagnosis of diabetes as well as 50 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Impairment of intracellular Ca 2+ homeostasis and mitochondrial function has been implicated in the development of LVH [28,29]. In our recent study [30] we have found that ADPKD patients with normal renal function had higher Ca 2+ concentrations in serum and erythrocytes and higher serum PTH levels (borderline significance) compared with non-ADPKD controls. This may indicate that the natural course of ADPKD leads to disorders of calcium metabolism preceding the onset of renal failure.…”
Section: Resultsmentioning
confidence: 93%
“…Impairment of intracellular Ca 2+ homeostasis and mitochondrial function has been implicated in the development of LVH [28,29]. In our recent study [30] we have found that ADPKD patients with normal renal function had higher Ca 2+ concentrations in serum and erythrocytes and higher serum PTH levels (borderline significance) compared with non-ADPKD controls. This may indicate that the natural course of ADPKD leads to disorders of calcium metabolism preceding the onset of renal failure.…”
Section: Resultsmentioning
confidence: 93%
“…Our study also revealed a correlation between osteocalcin level and inorganic P and between osteoprotegerin and inorganic P and CRP. In patients with CKD, it is well established that hyperphosphataemia is associated with the development of vascular calcification [ 38 , 44 , 77 82 ]. Recent studies have demonstrated that high extracellular phosphate levels induce the transformation of VSMCs into osteoblast-like cells, which suggests that vascular calcification is an active process.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic PKD1 or PKD2 mutations that abrogate complex formation, compromise cell surface expression of PKD1, or reduce TRPP2 channel activity suppress activation by WNTs [32]. It is worth noting that we have previously reported an increase in Ca 2+ concentration in the erythrocytes of our ADPKD patients with normal renal function [33].…”
Section: P R E P R I N Tmentioning
confidence: 68%